Lamothe family papers - Lamothe, Alexis de, 1728-1786.; Lamothe, Delphin de, 1725-1781.
Correspondence, poetry and folk songs, pamphlets, and notes relating primarily to brothers Alexis de Lamothe and Delphin Lamothe, both lawyers, and to their interest in the folk songs, poetry, and customs of the Bordeaux region. Also includes draft addresses (circa 1740-1760), some from the Parlement de Bordeaux, to bishops and various members of the French royal family.
Family residing in Bordeaux, France.
Collection material in French.
Calendar available in the Manuscript Reading Room.
Keywords: Lamothe family; France. -- Parlement (Bordeaux); Catholic Church -- France -- Bishops; Families of royal descent -- France; Folk songs, French -- France -- Bordeaux (Aquitaine).; French poetry -- France -- Bordeaux (Aquitaine).; Lawyers -- France -- Bordeaux (Aquitaine).; Bordeaux (Aquitaine, France) -- Social life and customs; France -- History -- 18th century; France -- Politics and government -- 18th century